Platelets enhance neutrophil transendothelial migration via P-selectin glycoprotein ligand-1 - Lam, Fong W. (American Physiological Society, 2011)
Platelets are increasingly recognized as important for inflammation in addition to thrombosis. Platelets promote the adhesion of neutrophils [polymorphonuclear neutrophils (PMNs)] to the endothelium; P-selectin and P-selectin glycoprotein ligand (PSGL)-1 have been suggested to participate in these interactions. Whether platelets also promote PMN transmigration across the endothelium is less clear. We tested the hypothesis that platelets enhance PMN transmigration across the inflamed endothelium and that PSGL-1 is involved. We studied the effects of platelets on PMN transmigration in vivo and in vitro using a well-characterized corneal injury model in C57BL/6 mice and IL-1β-stimulated human umbilical vein endothelial cells (HUVECs) under static and dynamic conditions. In vivo, platelet depletion altered PMN emigration from limbal microvessels after injury, with decreased emigration 6 and 12 h after injury. Both PSGL-1(−/−) and P-selectin(−/−) mice, but not Mac-1(−/−) mice, also had reduced PMN emigration at 12 h after injury relative to wild-type control mice. In the in vitro HUVEC model, platelets enhanced PMN transendothelial migration under static and dynamic conditions independent of firm adhesion. Anti-PSGL-1 antibodies markedly inhibited platelet-PMN aggregates, as assessed by flow cytometry, and attenuated the effect of platelets on PMN transmigration under static conditions without affecting firm adhesion. These data support the notion that platelets enhance neutrophil transmigration across the inflamed endothelium both in vivo and in vitro, via a PSGL-1-dependent mechanism.